Impact of sublethal levels of mercury on glycogen and selected respiratory enzymes in Heteropneustesfossilis and role of water hyacinth in reduction of Hg toxicity - James, R; Pattu, V Jancy; Devakiamma, G; Sampath, K (Indian Journal of Fisheries, 2011)
Mercury adversely affects various physiological and biochemical functions of fish (Snarski and Olson 1982; Muthukrishnan et al. 1986). Water hyacinth, Eichhornia erassipes, has been reported to have the capability of absorbing and removing someheavy metals from poUuted water bodies (Wolverton and McDoiaM 1975; Chigbo et al. 1982). However, studies on utilization of aquiUic plants fcff Ae reduction of mercury toxicity to fish are lacking. Tliis study rqx)its die sublethal effects of morury on glycogen and selected respirat(Â»y enzymes in Hetert^mustes fossilis and the role of wato- hyacindi in reducing the metal toxicity.